Taurine protects against methotrexate-induced toxicity and inhibits leukocyte death - YEGEN, BERRAK; ERCAN, FERİHA; ŞENER, GÖKSEL; ŞİRVANCI, SERAP (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2005)
The efficacy of methotrexate (MTX), a widely used cytotoxic chemotherapeutic agent, is often limited by severe side effects and toxic sequelae. Regarding the mechanisms of these side effects, several hypotheses have been put forward, among which oxidative stress is noticeable. The present study was undertaken to determine whether taurine, a potent free radical scavenger, could ameliorate MTX-induced oxidative injury and modulate immune response. Following a single dose of methotrexate (20 mg/kg), either saline or taurine (50 mg/kg) was administered for 5 days. After decapitation of the rats, trunk blood was obtained and the ileum, liver, and kidney were removed to measure malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity, and collagen content, as well as histological examination. Our results showed that MTX administration increased the MDA, MPO activity, and collagen contents and decreased GSH levels in all tissues (P < 0.001), while these alterations were reversed in taurine-treated group (P < 0.05-0.01). Elevated (P < 0.001) TNF-alpha level observed following MTX treatment was depressed with taurine (P < 0.01). Oxidative burst of neutrophils stimulated by phorbol myristate acetate was reduced in saline-treated MTX group (P < 0.001), while taurine abolished this effect. Similarly, flow cytometric measurements revealed that leukocyte apoptosis and cell death were increased in MTX-treated animals, while taurine reversed these effects (P < 0.05). Reduced cellularity in bone marrow samples of MTX-treated group (P < 0.01) was reversed back to control levels in taurine-treated rats. Severe degeneration of the intestinal mucosa, liver parenchyma, glomerular, and tubular epithelium observed in saline-treated group was improved by taurine treatment. In conclusion, it appears that taurine protects against methotrexate-induced oxidant organ injury and inhibits leukocyte apoptosis and may be of therapeutic potential in alleviating the systemic side effects of chemotherapeutics. (c) 2005 Published by Elsevier Inc.
Keywords: myeloperoxidase; glutathione; apoptosis; oxidative injury; IN-VITRO; INFLAMMATORY MEDIATORS; LYMPHOBLASTOID-CELLS; OXIDATIVE STRESS; INDUCED DAMAGE; NITRIC-OXIDE; RAT-KIDNEY; MYELOPEROXIDASE; HEPATOTOXICITY; CHLORAMINE